Rethinking academic identity: scholars as catalysts for institutional transformation in Zimbabwean higher education - Noah Ariel Mutongoreni; Charles Mbohwa (Cogent Education)
This study examines the pivotal role of academics in guiding the transformation of higher education in Zimbabwe amidst various challenges, including sanctions, the aftermath of COVID-19, energy shortages, macroeconomic instability, corruption, climate shocks, and a rising mental health crisis. As Zimbabwe reorients its higher education landscape, it becomes crucial to understand how academics can provide intellectual leadership in this transformation. Utilizing a mixed-methods approach, the research was conducted among academics from public and private universities accredited by the Zimbabwe Council for Higher Education (ZIMCHE). Data were collected through surveys, interviews, and document analysis, focusing on a purposively selected sample of 44 academics from 20 institutions. Findings indicate that while academics recognize their critical role in the transformation process, they face significant constraints, including political interference, restricted academic freedom, and limited involvement in policy formulation. This study emphasizes the need for democratisation of public spaces, opening dialogue on higher education transformation and advocates for academics to reclaim their position as intellectual leaders in the sector.